Welding effect on crack growth behavior and lifetime assessment of PE pipes. (July 2016) - Li, Haijing; Gao, Bingjun; Dong, Junhua; Fu, Yang
Abstract: Pressurized polyethylene (PE) pipes are widely used in many fields all over the world, in which welding process is employed frequently. The welding will probably cause unnegligible degradation of material properties. So figuring out the welding effect on PE material is essential to assure its integrity. In this work a typical commercial PE100 material was tested by a generally accepted testing method, Cracked Round Bar (CRB) test, under cyclic loading to make lifetime prediction of parent and welded PE material. Afterwards, fracture surfaces of all specimens have been examined by scanning electron microscopy(SEM) and was analyzed contrastively to illuminate the welding effect on the lifetime expectation of this kind of PE material.